The Leadership Behavior of Madrasah Principals in Enhancing the Commitees in Jambi Province - Wardatul Jannah; Mukhtar Mukhtar; Wahyudi Wahyudi; Boby Yasman Purnama (Edumaspul: Jurnal Pendidikan, 2024)
Madrasah Aliyah plays a vital role in shaping the future generations of Indonesia, especially in fostering academic excellence and religious values. However, in Jambi Province, the commitment of madrasah committees to support the programs of Madrasah Aliyah has been hindered by various challenges, such as limited participation, a lack of synergy with school principals, and minimal innovation in communication patterns. This study explores how the leadership behavior of madrasah principals can influence the commitment of committees in Jambi Province. The research adopts a qualitative descriptive approach with purposive sampling, involving principals, committee members, and teachers. Data was collected through interviews, participatory observation, and document analysis. The findings show that principals who engage committees in decision-making, encourage open communication, and integrate religious values into their leadership behavior are more successful in enhancing committee commitment. This study contributes to the development of leadership models that incorporate local culture and Islamic values, offering practical guidance for madrasah principals to foster better collaboration and management.